Human development: a key driver of socioeconomic development in EU - Maria-Daniela Tudorache (Conference Proceedings of 13th Economics & Finance Virtual Conference, 2020)
This paper examines the economic development drivers and the ones of the social development in order to check if there is a potential trade-off between these development forms at the level of European Union, with a focus on human development and technological progress. In this context, I have used panel yearly data covering the period 2010-2018 for EU Member States. Both models were estimated using Panel Estimated Generalized Least Squares and some weighting options as Period SUR and Cros-section weights. However, the specificities of the data led to a different application of the methods in the case of the mentioned models. In this regard, I have run a Fixed Effects Model in studying the determinants of economic development and a None Effects Model when analysing the drivers of social development. The main results of the paper showed a positive relationship between human development and social and economic development. In adition, the study estimated a positive impact of ITC sector on economic development and a negative one on the poverty rate. However, the negative impact of ITC on social development is quite low and it may also include a positive impact on poverty (lower than the one manifested through the opportunities channel) exercised by automation, but this needs to be further explored. Both models provided feasible results which strengthens the confidence in the examined relationships.
Keywords: O15; C33; P46; 330; human development; growth; poverty; panel; European Union